2017
DOI: 10.1002/celc.201700842
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Self‐Polymerization Enables an N‐Doped Carbon Coating of Exfoliated MoS2 Nanoflakes for Anodes of Lithium‐Ion Batteries

Abstract: The molybdenum sulfide has a layered structure, similar to graphite, and delivers a good transfer channel for lithium ions as an anode. To enhance the discharge capacity and cycling stability of the molybdenum sulfide, exfoliated MoS2 nanoflakes with a N‐doped carbon coating were prepared by exfoliation of bulk MoS2 and carbonization of a polydopamine coating. The morphological characteristics show that the carbonized polydopamine was coated on the surface of MoS2 nanoflakes successfully. Consequently, as‐prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…The low-intensity peaks at ∼229.6 and ∼232.9 eV are attributed to Se 3s and Mo 6+ 3d 5/2 states, respectively. , The highly intense peak for the Mo 4+ state indicates the formation of MoSe 2 , while a weak one for the Mo 6+ state reveals the fractional presence of molybdenum oxide (MoO 3 ) at the NC outer shell due to the surface oxidation in a laboratory ambient. Intriguingly, the signal from Mo 6+ 3d 3/2 states (∼235.9 eV) is feeble; however, similar observations have been reported previously. , Similarly, the Se 3d spectrum has been deconvoluted into Se 3d 5/2 and 3d 3/2 peaks centered at ∼54.0 and ∼55.0 eV, respectively, suggesting the formation of the Se 2– state of MoSe 2 , which is in good agreement with existing reports. , The absence of any other unwanted elements indicates the chemical purity and stoichiometry of exfoliated NCs. Deconvoluted XPS spectra for other samples are shown in Figure S4, and it is found that the NCs having an average size of ∼50, ∼12, and ∼5 nm contain approximately ∼5.8, ∼9.6, and ∼12% of oxygenated-Mo (Mo 6+ ), respectively.…”
Section: Results and Discussionsupporting
confidence: 92%
“…The low-intensity peaks at ∼229.6 and ∼232.9 eV are attributed to Se 3s and Mo 6+ 3d 5/2 states, respectively. , The highly intense peak for the Mo 4+ state indicates the formation of MoSe 2 , while a weak one for the Mo 6+ state reveals the fractional presence of molybdenum oxide (MoO 3 ) at the NC outer shell due to the surface oxidation in a laboratory ambient. Intriguingly, the signal from Mo 6+ 3d 3/2 states (∼235.9 eV) is feeble; however, similar observations have been reported previously. , Similarly, the Se 3d spectrum has been deconvoluted into Se 3d 5/2 and 3d 3/2 peaks centered at ∼54.0 and ∼55.0 eV, respectively, suggesting the formation of the Se 2– state of MoSe 2 , which is in good agreement with existing reports. , The absence of any other unwanted elements indicates the chemical purity and stoichiometry of exfoliated NCs. Deconvoluted XPS spectra for other samples are shown in Figure S4, and it is found that the NCs having an average size of ∼50, ∼12, and ∼5 nm contain approximately ∼5.8, ∼9.6, and ∼12% of oxygenated-Mo (Mo 6+ ), respectively.…”
Section: Results and Discussionsupporting
confidence: 92%
“…Remarkably, in opposite to Ni 2p and W 4f, a negative shift of about −0.2 and −0.6 eV is seen in Mo 3d and S 2p of the Ag-MRGON heterojunction compared with the MoS 2 /NiWO 4 heterojunction and pristine MoS 2 (Figure S4d,e), respectively, suggesting the increase in the electron density of MoS 2 and successful heterojunction formation . The BE values of Mo 3d and S 2p are in close agreement with the previously published values. , Similar to Mo 3d and S 2p, the Ag 3d XPS spectrum (Figure h) was fitted into two doublet peaks positioned at 366.8 and 372.8 eV, which can be, respectively, assigned to Ag 3d 5/2 and Ag 3d 3/2 of metallic Ag 0 . These BE values are positively shifted by 0.6 eV than the literature values of metallic silver NPs indicating the electron transfer from Ag NPs to MoS 2 NS and NiWO 4 NPs.…”
Section: Results and Discussionsupporting
confidence: 90%
“…31 The BE values of Mo 3d and S 2p are in close agreement with the previously published values. 48,49 Similar to Mo 3d and S 2p, the Ag 3d XPS 41,51 However, no clear plasmonic peak appears in the spectrum because of the possible aggregation of the Ag NPs. On the other hand, it is worth emphasizing that RGO does not contribute to the light absorption because of the absence of the absorption edge of RGO in the UV−vis DRS spectrum of Ag-MRGON.…”
Section: Resultsmentioning
confidence: 96%
“…However, the existence of PDA affected the crystallinity of the MoS 2 crystal [ 27 ]. The introduction of carbon would lead to the reduction of the diffraction peak [ 36 ]. Due to the deposition of dopamine, the carbon element increased, the purity of MoS 2 crystal decreased, and the intensity of the diffraction peak reduced.…”
Section: Resultsmentioning
confidence: 99%
“…However, the intensity of O1s and C1s were enhanced, and we confirmed the production of dopamine-induced polymerization, which was coated on the MoS 2 surface. The high-resolution Mo 3d spectra ( Figure 5 b) had three peaks; 229.34 eV and 232.51 eV related to Mo 4+ 3d 5/2 and Mo 4+ 3d 3/2 , while the peak at 235.59 eV may be derived from the surface oxidation of Mo 6+ [ 36 , 39 ]. In the spectra of the high-resolution S 2p ( Figure 5 c), there were peaks at 162 eV and 163.3 eV corresponding to the bivalent S 2p 3/2 and S 2p 1/2 (S 2− ) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%